A study on the relationship between language aptitude, vocabulary size, working memory, and L2 writing accuracy. (25th October 2021) - Mujtaba, Syed Muhammad; Kamyabi Gol, Atiyeh; Parkash, Rakesh
Abstract: The area of individual differences (ID) in second language (L2) has been a point of interest for many researchers; however, the impact of ID on the writing performance of L2 learners has not been explored exhaustively. Only a limited number of studies have examined the role of language aptitude, vocabulary size, and working memory (WM) on L2 learners' writing accuracy. The current study aimed to investigate the effects of language aptitude, vocabulary size, and WM on L2 learners' writing accuracy. For that, fifty graduate first‐semester students were recruited and took the WM, LLAMA, and a vocabulary test. Subsequently, they completed two picture description writing tasks. The Pearson correlation result unveiled that all the independent variables excluding LLAMA D were significantly correlated with learners' writing performance. The regression analysis result explained that LLAMA B, LLAMA E, receptive vocabulary size, and WM were strong predictors of learners' L2 writing performance. The Challenge: Individual differences in second language have been a point of interest for many researchers; however, there are only a limited number of studies which have explored its role in second language writing. The current study investigated the effects of language aptitude, vocabulary size, and working memory on second language writing performance.